Adverse drug reaction assessment of pembrolizumab in cervical cancer treatment: a real-world pharmacovigilance study using the FAERS database - Zhang, Huiping; Zhou, Zhuo; Wang, Juan; Wang, Shan; Ren, Jie; Zhang, Ming; Yang, Mingyi (Frontiers in Immunology, 2025)
ObjectiveAdvanced cervical cancer remains associated with high mortality rates. While pembrolizumab has improved clinical outcomes in cervical cancer, the therapeutic efficacy in advanced stages is often compromised by immune-related adverse events (irAEs). This study aimed to systematically analyze pembrolizumab-associated adverse events (AEs) in cervical cancer using the FDA Adverse Event Reporting System (FAERS) database, providing new insights for optimizing clinical practice.MethodsAE reports related to pembrolizumab in cervical cancer were extracted from the FAERS database (Q1 2016 to Q4 2024). Disproportionality analyses were performed using multiple algorithms, including the reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS). AEs were classified by system organ class (SOC) and preferred term (PT) based on the Medical Dictionary for Regulatory Activities (MedDRA), then ranked by frequency and signal strength.ResultsA total of 646 pembrolizumab-related AE reports in cervical cancer were identified. Age distribution peaked at 45–65 years cohort (32.75%), followed by 18–44 years (12.85%), 66–75 years (11.76%), and >75 years (4.64%). Among 270 AE reports with documented onset timelines, events predominantly occurred 3–6 months after pembrolizumab initiation (n=114, 41.36%). Clinical outcomes were categorized as other (52.80%), hospitalization (27.00%), death (10.25%), unknown (6.06%), life-threatening (2.77%), and disability (1.12%). Predominant AEs involved hematologic, endocrine, dermatologic, neurologic, gastrointestinal, urinary, and reproductive systems.ConclusionThis real-world pharmacovigilance study systematically characterizes pembrolizumab-associated AEs in cervical cancer, identifying high-signal events such as hematologic disorders, endocrine dysfunction, and dermatologic toxicities. These findings provide critical evidence for risk stratification and safety monitoring in clinical practice, emphasizing the need for organ-specific vigilance during the 3–6 months treatment window.